Peranan Ustadz Ustadzah dalam Pembinaan Hafalan Al Qur'an Siswa Kelas 1 MI Terpadu Al Ma'shum Surakarta - Kinesti, Rakanita Dyah Ayu; Yahya, Rosalia Indiani; Arifin, Faizal; Isnaini, Selma Putri (Lembaga Yasin AlSys, 2023)
The problem of this research is what is the role of ustadz ustadzah in implementing the tahfidz program to improve the ability to read and memorize the Qur'an for young children at the Integrated Tahfidz Al Qur'an Al Ma'shum Surakarta Madrasah Ibtidaiyah? The type of research conducted is descriptive research which is then carried out using the CSR (Case Study Research) strategy and the focus or core of this research is to see and find out how the role of the ustadzah in carrying out their duties, roles and functions is as a facilitator, manager, mentor and evaluator. Then for the types of data that exist in this study are data in the form of primary data and secondary data, while the information obtained is data collected from observations in the field and also interviews with informants. The informants selected by the researchers included: Ustadz / Ustadzah (Educators) from the Madrasah Ibtidaiyah Integrated Tahfidz Al Qur'an Al Ma'shum Surakarta (Ustadzah who teaches Tahfidz in grade 1), while for data obtained through observation, observations were made, namely in class 1.